Dysmetabolic Hyperferritinemia and Dysmetabolic Iron Overload Syndrome (DIOS): Two Related Conditions or Different Entities? - Rametta, Raffaela; Fracanzani, Anna L.; Fargion, Silvia; Dongiovanni, Paola (Current Pharmaceutical Design, 2020)
Hyperferritinemia is observed in one-third of patients with non-alcoholic fatty liver disease (NAFLD) and Metabolic Syndrome (MetS). The condition characterized by increased body iron stores associated with components of MetS has been defined as Dysmetabolic Iron Overload Syndrome (DIOS). DIOS represents the most frequent iron overload condition, since it is observed in 15% of patients with MetS and in half of those with NAFLD and its clinical presentation overlaps almost completely with that of dysmetabolic hyperferritinemia (DH). The pathogenetic mechanisms linking insulin resistance (IR), NAFLD and DIOS to iron overload are still debated. Hepcidin seems to play a role in iron accumulation in DIOS and NAFLD patients who show elevated serum hepcidin levels. The iron challenge does not restrain iron absorption despite adequate hepcidin production, suggesting that an impaired hepcidin activity rather than a deficit of hormone production underlies DIOS pathogenesis. Acquired and genetic factors are recognized to contribute to iron accumulation in NAFLD whereas additional studies are required to clearly demonstrate whether the same or different genetic factors lead to iron overload in DIOS. Finally, iron depletion by phlebotomy, together with the modification of diet and life-style habits, represents the therapeutic approach to decrease metabolic alterations and liver enzymes in NAFLD and DIOS patients. In this review, we summarized the current knowledge on the dysregulation of iron homeostasis in NAFLD and DIOS in the attempt to clarify whether they are different or more likely strictly related conditions, sharing the same pathogenic cause i.e. the MetS.
Keywords: ferritin